PERILAKU KECANDUAN MENONTON DRAMA KOREA DAN HUBUNGAN SOSIAL PADA SISWA SMPN 13 PEKANBARU - Wika Bia Adita; Rosmawati Rosmawati; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the behavior of addiction to watching Korean-drama and social relationships on SMPN 13 Pekanbaru.this research is done because of the increasingly widespread Korean wave in Indonesia that makes teenagers the main target. The school where the research was carried out many consequences arising from Korean wave for example students prefer to spend time in class to watch the Korean drama rather than playing with his friend. One of the effects of watchingKorean dramas is the growing individual consumptive towards Korean dramas that neglect their social relationships with the environment. The aim of the research is to know the description of the addiction behavior of watching Korean drama and the image of social relations of students who are addicted to watching Korean drama. The results of data analysis of the addiction rate watching Korean drama show that the image of addiction behavior watching Korean drama students is in the moderate category with the percentage of 60,87% and the social relations of students who are addicted to watching Korean drma >6 episodes of students have a good social relationship with a percentage of 56,52%. Key words : Addicted, Social Relationships, Korean-drama